A novel porcine kobuvirus emerged in piglets with severe diarrhoea in China. Issue 4 (11th May 2017) - Zhai, S.‐L.; Zhang, H.; Lin, T.; Chen, S.‐N.; Zhou, X.; Chen, Q.‐L.; Lv, D.‐H.; Wen, X.‐H.; Zhou, X.‐R.; Jia, C.‐L.; Wei, W.‐K.
Summary: Since the first report of porcine kobuvirus (PKV) in 2008, it has been confirmed that PKV is widely present in several countries and plays an important role in diarrhoea outbreak in pigs. Studies have shown that the biggest difference among PKVs is the presence or absence of a specific 30‐amino acid (aa) sequence in the 2B region of the polyprotein gene. Based on this unique feature, most PKV sequences could be divided into two groups (Group 1 without deletion and Group 2 with deletion), but a few sequences did not follow this rule due to possible recombination. In this study, two PKV genome sequences, designated JXAT2015 (8, 123 nucleotide) and JXJC2015 (8, 120 nucleotide), were identified on two different commercial swine farms with the severe diarrhoea outbreak accompanying with highly PKV infection (90%, 18/20) and moderate infection (40%, 8/20) of porcine bocavirus 1 (PBoV1) in Jiangxi province of China. Sequence analysis based on the polyprotein gene showed that they shared low nucleotide similarity (86.3%–88.1%) with other known PKVs. Although both possessed the 30‐aa deletion in the 2B region, phylogenetic analysis showed that JXJC2015 was distinct from Group 1 and even Group 2, and formed a new Group (designated Group 3). The findings of this study further revealed genetic diversity and the possible pathogenic role of PKV in conjunction with other pathogens in piglets.